2007
DOI: 10.1098/rspb.2007.0170
|View full text |Cite
|
Sign up to set email alerts
|

Song repertoire size varies with HVC volume and is indicative of male quality in song sparrows (Melospiza melodia)

Abstract: Complex birdsong is a classic example of a sexually selected ornamental trait. In many species, females prefer males with large song repertoires, possibly because repertoire size is limited by the size of song control nuclei which reflect developmental success. We investigated whether song repertoire size was indicative of brain area and male quality in song sparrows (Melospiza melodia) by determining if repertoire size was related to the volume of song control nucleus HVC, as well as several morphological, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 41 publications
3
70
2
Order By: Relevance
“…However, the association between oxidative damage and song performance may be related to the song repertoire of the individual or the species. For example, individuals with limited repertoires, due to e.g., developmental constraints (Pfaff et al, 2007;Peters et al, 2014;Schmidt et al, 2014) may consistently repeat the same motif thereby inducing muscular fatigue and oxidative damage. In such a case it is possible that oxidative damage experienced during development and manifested for example by telomere shortening or other extensive oxidative damage, overlaps with currently ongoing oxidative stress.…”
Section: Disentangling the Complexity Of Birdsong In Relation To Oxidmentioning
confidence: 99%
“…However, the association between oxidative damage and song performance may be related to the song repertoire of the individual or the species. For example, individuals with limited repertoires, due to e.g., developmental constraints (Pfaff et al, 2007;Peters et al, 2014;Schmidt et al, 2014) may consistently repeat the same motif thereby inducing muscular fatigue and oxidative damage. In such a case it is possible that oxidative damage experienced during development and manifested for example by telomere shortening or other extensive oxidative damage, overlaps with currently ongoing oxidative stress.…”
Section: Disentangling the Complexity Of Birdsong In Relation To Oxidmentioning
confidence: 99%
“…During the early months of life, the brain nuclei associated with song learning grow rapidly and appear particularly sensitive to food intake rate (Nowicki et al 1998(Nowicki et al , 2002. MacDonald et al (2006), for example, showed that HVC (song control nuclei) volume was greater in song sparrow (Melospiza melodia) nestlings fed ad libitum compared with a food-restricted group (HVC volume being correlated with song repertoire size in the field; Pfaff et al 2007). Female song sparrows prefer large song repertoires (Reid et al 2004), and repertoire size is highly predictive of lifetime reproductive success (Reid et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study of blue tits (Cyanistes caeruleus) demonstrated parasite load to be positively related to a physiological marker of stress (heat shock proteins) and inversely to sexually selected colouration [50]. Conversely, a study of song sparrows (Melospiza melodia) reported no relationship between stress and immune function [51], meaning that detrimental effects of stress on song repertoire were not mediated by immunocompetence. In our work with human faces, my colleagues and I found that the pattern of the interaction between testosterone and cortisol on attractiveness was mirrored by the same pattern in effects on antibody response to a vaccine [43].…”
Section: Immunocompetencementioning
confidence: 99%
“…body mass and/or fat stores), an individual who is experiencing stress is less likely to be able to afford to allocate energy and metabolic resources to sexual signalling. Effects of stress on body condition, however, are inconsistent, with studies from some species showing that stress reduces body condition (song sparrow (Melospiza melodia) [51]; upland geese (Chloephaga picta) [52]; zebra finches [53]), others showing stress to increase body condition (Beldings ground squirrels (Spermophilus beldingi) [54]) and still others showing no effect (e.g. mallard ducks (Anas platyrhynchos) [55]).…”
Section: Stress and Body Conditionmentioning
confidence: 99%